Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Sejarah Lokal pada Materi Kolonialisme di Madrasah Aliyah Se-Kecamatan Stabat - Hartanto, Deni; Veronika, Nabila; Novianti, Yusda (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
This study aims to develop a Student Worksheet (LKPD) focused on local history, specifically addressing colonialism topics. The objective is to determine the validity and feasibility of the LKPD through evaluations by material and media experts, as well as through limited trials conducted with students from Madrasah Aliyah in Stabat District. This study employs research and development (R&D) methodologies. The developed LKPD underwent validation by two experts: material experts and media experts. The validation results indicated that in the second validation, the material expert assigned a feasibility percentage of 91%, categorized as